Hydatid cyst of the heart located in the left ventricle. Operation - healing - Bosch del Marco, Luis M; Canabal, Eduardo Joaquín; Dighiero, Jorge; Baldomir, josé María; Suzacq, Carlos V; Antiga, Pedro F (Cirugía del Uruguay, 2020)
Presented at session 24th October 1951